Role of depressive symptoms in subjective memory complaint in older adults with mild cognitive impairment. (19th November 2019) - Song, Dan; Yu, Doris S. F.; Li, Polly W. C.; He, Guijuan; Shen, Cuizhen; Chen, Guolin; Sun, Qiuhua
Abstract: Aims: To explore the independent relationship between depressive symptoms and subjective memory complaint (SMC) amongst older adults with mild cognitive impairment (MCI) after adjusting for objective cognitive function and other important confounding factors. Background: subjective memory complaint is a core symptom of MCI and is often the primary reason for older adults with MCI to seek for medical help. Improving subjective memory amongst older adults with MCI is important to enhance their quality of life and potentially delay further cognitive decline. Depressive symptoms, which are highly prevalent neuropsychiatric symptoms amongst older adults with MCI, may be one of the reasons that affect an individual's self‐perception of memory function. However, there is a dearth of studies to provide a thorough evaluation of the independent relationship between depressive symptoms and SMC amongst older adults with MCI. Design: A descriptive correlational study. Methods: A consecutive sample ( N = 154) of adults aged over 60 years was recruited from a community healthcare centre between June and September 2016. MCI was detected using the Montreal Cognitive Assessment. Depressive symptoms and subjective memory were measured using the Geriatric Depression Scale and Memory Inventory for the Chinese, respectively. Hierarchical regression was performed to explore the relationship between SMC and depressive symptoms, with control over objective cognitive function, socio‐demographic and health‐related confounding factors. Results: After controlling objective cognitive function and other confounding factors, SMC was independently associated with depressive symptoms (standardised β = 0.336, p < .001). This psychological status even explained for a greater variance ( R 2 = 8.8%) for SMC compared with objective cognitive function ( R 2 = 2.4%). Conclusion: subjective memory complaint was independently associated with depressive symptoms in older adults with MCI. Early detection and management of depressive symptoms are highly important amongst this clinical cohort. Implications for practice: Early detection and prompt treatment of depressive symptoms is a highly prioritised care agenda in managing SMC in older adults with MCI.